Geographical education and visual pedagogy in the photographs of National Geographic Magazine: three discussions placed in dialogue (PerCursos, 2025)
This article addresses geographical education focused on the idea of visual pedagogy through photographs published in National Geographic Magazine, based on three theoretical discussions from different mediums (audiovisual, book, and article) that have focused on the photographic images in the magazine. The magazine is treated here as a potential platform where we can find photographic images that educate a society thirsty for learning. Drawing on the works of Daniel Tröhler, Julio Groppa Aquino, Dora Lilia Marín-Díaz, and Carlos Ernesto Noguera-Ramírez, the premise is that there is currently a proliferation and dispersion of educational environments, artifacts, and technologies beyond formal educational settings. In this sense, the photographs in the magazine are considered not only as a resource for scientific info-entertainment for a select interested audience but primarily as agents that create geographies, ways of looking at and inhabiting geographical space through visual pedagogy. The overarching questions are: How do images educate about geographies? How do the photographs in the magazine transform space? This qualitative documentary research engages in a dialogue about the photographic images in the magazine conducted by three researchers: the images of primatologist Jane Goodall analyzed in a TV program, the iconic cover of the Afghan girl discussed in a book, and the peoples of the Middle East in a scientific article. As a result, we understand that the magazine creates a notion of truth through its photographic images, educates ways of seeing and what should be seen, and establishes a visual pedagogy that creates geographies about places, peoples, and cultures.
Keywords: photographic images; visibility regimes; lifelong learning